Examining the Human Resource Architecture: The Relationships Among Human Capital, Employment, and Human Resource Configurations - Lepak, David P.; Snell, Scott A. (Journal of Management, 2002)
In this study we examined the characteristics of human capital as well as the human resource (HR) configurations used for employees in four different employment modes (knowledge-based employment, job-based employment, contract work, and alliance/partnership). Results from 148 firms show that the strategic value and uniqueness of human capital differs across these four employment modes. In addition, each employment mode is associated with a particular type of HR configuration (commitment-based, productivity-based, compliance-based, and collaborative).